Mathematical theory of subdivision : finite element and wavelet methods - Kumar, Sandeep (Professor of mechanical engineering); Pathak, Ashish; Khan, Debasish (Boca Raton, Florida : CRC Press, 2019)
This book provides good coverage of the powerful numerical techniques namely, finite element and wavelets, for the solution of partial differential equation to the scientists and engineers with a modest mathematical background. The objective of the book is to provide the necessary mathematical foundation for the advanced level applications of these numerical techniques. The book begins with the description of the steps involved in finite element and wavelets-Galerkin methods. The knowledge of Hilbert and Sobolev spaces is needed to understand the theory of finite element and wavelet-based methods. Therefore, an overview of essential content such as vector spaces, norm, inner product, linear operators, spectral theory, dual space, and distribution theory, etc. with relevant theorems are presented in a coherent and accessible manner. For the graduate students and researchers with diverse educational background, the authors have focused on the applications of numerical techniques which are developed in the last few decades. This includes the wavelet-Galerkin method, lifting scheme, and error estimation technique, etc. Features: Computer programs in Mathematica/Matlab are incorporated for easy understanding of wavelets. Presents a range of workout examples for better comprehension of spaces and operators. Algorithms are presented to facilitate computer programming. Contains the error estimation techniques necessary for adaptive finite element method. This book is structured to transform in step by step manner the students without any knowledge of finite element, wavelet and functional analysis to the students of strong theoretical understanding who will be ready to take many challenging research problems in this area.
Preface About the authors 1. Overview of finite element method Some common governing differential equations Basic steps of finite element method Element stiffness matrix for a bar Element stiffness matrix for single variable 2d element Element stiffness matrix for a beam element References for further reading 2. Wavelets Wavelet basis functions Wavelet-Galerkin method Daubechies wavelets for boundary and initial value problems References for further reading 3. Fundamentals of vector spaces Introduction Vector spaces Normed linear spaces Inner product spaces Banach spaces Hilbert spaces Projection on finite dimensional spaces Change of basis -- Gram-Schmidt othogonalization process Riesz bases and frame conditions References for further reading 4. Operators Mapping of sets, general concept of functions Operators Linear and adjoint operators Functionals and dual space Spectrum of bounded linear self-adjoint operator Classification of differential operators Existence, uniqueness and regularity of solution References 5. Theoretical foundations of the finite element method Distribution theory Sobolev spaces Variational Method Nonconforming elements and patch test References for further reading 6. Wavelet- based methods for differential equations Fundamentals of continuous and discrete wavelets Multiscaling Classification of wavelet basis functions Discrete wavelet transform Lifting scheme for discrete wavelet transform Lifting scheme to customize wavelets Non-standard form of matrix and its solution Multigrid method References for further reading 7. Error -- estimation Introduction A-priori error estimation Recovery based error estimators Residual based error estimators Goal oriented error estimators Hierarchical & wavelet based error estimator References for further reading Appendix
OCLC-licensed vendor bibliographic record.
Keywords: Finite element method; Wavelets (Mathematics); Numerical analysis; Harmonic analysis; Generalized spaces; MATHEMATICS / General; MATHEMATICS / Applied; MATHEMATICS / Number Systems